Multi-Platform Strategies of Populis Figur in West Sumatra - Lestari, Yayuk; Diego, Diego; Okditazeini, Vannyora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This article explores the digital strategies of Islamic populism in West Sumatra by examining how key figures such as Fauzi Bahar and Jel Fathullah systematically leverage social media platforms to disseminate moral discourses grounded in the local religious-philosophical paradigm of Adat Basandi SyaraÔÇÖ, SyaraÔÇÖ Basandi Kitabullah (ABS-SBK). Drawing on a descriptive qualitative approach through digital observation, the study reveals a multi-platform orchestration in which Facebook functions as a site for constructing long-form religious narratives and symbolic continuity, while Instagram Reels and TikTok are deployed for affective mobilization through short, emotionally charged content featuring themes such as hijrah, almsgiving, and Islamic virtue. The interplay of symbolic messaging and technical affordances across platforms illustrates what scholars have termed symbolic convergenceÔÇöa synchronization of religious rhetoric with platform-specific features to consolidate affective publics. The analysis demonstrates how figures like Jel Fathullah transform short-form visual content into emotional gateways that channel followers toward deeper ideological engagements via Facebook Live or digital sermons. User engagement through likes, shares, and comments is interpreted by followers as a form of